Electricity generation prospects from clustered smallholder and irrigated rice farms in Ghana. (15th February 2017) - Arranz-Piera, Pol; Kemausuor, Francis; Addo, Ahmad; Velo, Enrique
Abstract: In farming communities in Ghana and the West African region, crop residues are often unused and remain available for valorisation. This study has analysed the prospects of electricity generation using crop residues from smallholder farms within defined clusters. Data was collected from 14 administrative districts in Ghana, where surveys were conducted and residue-to-product ratios determined in farmer fields. Thermochemical characterisation of residues was performed in the laboratory. The number of clustered farms, reference residue yields and residue densities were determined to assess the distances within which it would be feasible to supply feedstock to CHP plants. The findings show that in most districts, a minimum of 22–54 larger (10 ha) farms would need to be clustered to enable an economically viable biomass supply to a 1000 kWe plant. A 600 kWe plant would require 13 to 30 farms. Financial analysis for a 1000 kWe CHP plant case indicate that such investment would not be viable under the current renewable feed-in-tariff rates in Ghana; increased tariff by 25% or subsidies from a minimum 30% of investment cost are needed to ensure viability using internal rate of return as an indicator. Carbon finance options are also discussed. Highlights: Electricity generation from smallholder farms crop residues has been analysed. Field data was collected from 14 administrative districts in Ghana. Crop residues from 22 to 54 clustered farms (10 ha) are needed to run a 1MWe plant. Financial viability of a 1MWe CHP plant is not possible under current Feed-in Tariff levels. A 25% increase of current FiT or 30% subsidy on investment costs would be needed.